2011
DOI: 10.1159/000325216
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Serotonin Transport in Human Platelets by Tyrosine Kinase Syk

Abstract: Serotonin (5-hydroxytryptamine, 5-HT) is a neurotransmitter involved in the regulation of numerous neuro-physiological processes. The circulating level of 5-HT is regulated by the membrane transporter SERT present both in the presynaptic nerve terminals and blood platelets. 5-HT transport is a process tightly regulated by a variety of factors including protein phosphorylation. Aim of this study was to ascertain if also the SERT Tyr-phosphorylation mediated by Syk-kinase concurs to the regulation of SERT activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 56 publications
1
14
0
Order By: Relevance
“…Interestingly, a reduction in imipramine binding sites was observed after PP2/SU6656 treatments, suggesting a change in SERT conformation may attend transporter Tyr phosphorylation. Pavanetto et al (2011) also reported evidence of P-Tyr incorporation in human platelet SERT by immunoblotting of SERT immunoprecipitates, with evidence presented indicating a decrease in labeling from platelets treated with the Syk kinase inhibitor piceatannol, paralleling reductions in 5-HT uptake. Corroborative findings of piceatannol-induced reductions in SERT phosphorylation were also obtained using a metabolic labeling strategy.…”
Section: Evidence Of Tyrosine Phosphorylation Of Monoamine Transpomentioning
confidence: 87%
See 1 more Smart Citation
“…Interestingly, a reduction in imipramine binding sites was observed after PP2/SU6656 treatments, suggesting a change in SERT conformation may attend transporter Tyr phosphorylation. Pavanetto et al (2011) also reported evidence of P-Tyr incorporation in human platelet SERT by immunoblotting of SERT immunoprecipitates, with evidence presented indicating a decrease in labeling from platelets treated with the Syk kinase inhibitor piceatannol, paralleling reductions in 5-HT uptake. Corroborative findings of piceatannol-induced reductions in SERT phosphorylation were also obtained using a metabolic labeling strategy.…”
Section: Evidence Of Tyrosine Phosphorylation Of Monoamine Transpomentioning
confidence: 87%
“…How these findings in rat platelets and transfected cells relate to the more rapid effects detected in human platelets is as yet unclear and should be further pursued. Rapid (minutes) inhibitory effects on 5-HT uptake have also been reported after treatment of human platelets with inhibitors of the intracellular TK Syk (Pavanetto et al, 2011), suggesting that SERT proteins, at least in platelets, may be the target of multiple cytosolic TKs. A reduced 5-HT uptake V max was reported after Syk inhibition in the latter study, which the authors attribute to stabilization of the transporter in an inward-facing conformation, due to a loss of imipramine binding sites, although the whole cell nature of the binding studies precludes elimination of SERT internalization as a possible explanation.…”
Section: A Pharmacological Evidence For Tyrosine Kinase Modulation Omentioning
confidence: 93%
“…Syk is activated after the binding of fibrinogen to integrin α IIb β 3 [26]. Recently, Pavanetto and colleagues reported that in human platelets Syk is co-immunoprecipitated with the antibody raised against serotonin transporter and regulates the activity of serotonin transporter [27]. In addition, direct interaction between serotonin transporter and integrin α IIb β 3 has been previously identified [21].…”
Section: Discussionmentioning
confidence: 98%
“…Consequently, Syk and 5-HTT interaction seems to be dispensable for the initial activation of GPVI complex, but enhanced Syk activity may regulate the 5-HT uptake in platelets [29].…”
Section: +mentioning
confidence: 98%